Liver abscess associated with severe myopathy caused by Klebsiella pneumoniae serotype K1 in Romania - Gabriel-Adrian Popescu; Diana Tanase; Ana-Maria Petrescu; Dragos Florea (Journal of Infection in Developing Countries)
Liver abscess was diagnosed in a man presenting with fever, chills and severe myopathy. The K. pneumoniae isolated from blood cultures belonged to the K1 serotype. The patient responded favourably to percutaneous drainage of the abscess and antibiotics. This is the first documented report of Klebsiella pneumoniae liver abscess syndrome (KLAS) described in Romania and may indicate the emergence of this syndrome in Eastern Europe.